Avaliação de diferentes complexos biológicos no controle de pérola da terra (Eurhizococcus brasiliensis (Wille, 1922)) na cultura de Vitis vinifera - cultivar chardonnay - Venturin, Leandro (My University, 2025)
One of the challenges of current agriculture is the production of food with less interference with the agricultural system. The implementation of ecologically based/regenerative agricultural practices is essential for achieving healthy and more resilient production systems. In this sense, understanding strategies to control the pest Eurhizococcus brasiliensis is necessary. The objective of this work was to analyze the impact of different inoculants on the development of Vitis vinifera from the Chardonnay cultivar and evaluate the diversity of microorganisms involved in the suppressiveness of E. brasiliensis. In the field experiment, biological inputs were used by immersion or application in the cradle of the root system, by Trichoderma sp, Metarhizium sp, Beauveria bassiana, Paecilomyces fumosoroseus, in addition to other compounds such as Hidrogel®, Compost Aid®, biofertilizer based on castor beans , Nem Out®, Microgeo®, CMM - Microbial Complexes and their Metabolites, and EMN - Efficient Microorganisms Natives. The diversity of cultivable microorganisms, identified by 16S rDNA analysis, for bacteria and ITS for fungi or microbial communities by metagenomics, in material from microbial fermentations and in soil treatments, was evaluated. Length of branches, number of leaves, population of earth pearl cysts and dead vine plants after 22 months of planting the seedlings were also evaluated. Using the methodology for analyzing cultivable microorganisms, it was possible to identify different groups of bacteria from the EMN (EM), CMM (FC), soil, SEF (Soil + CMM + EMN) and SFM (Soil + CMM + Microgeo) samples. They are mainly represented by the phyla Firmicutes, Proteobacteria, followed by Mycobacterium and Pseudomonadota among others. The genera Pseudomonas, Acinetobacter and Comamonas, representatives of the Phylum Proteobacteria, were also identified, followed by the genus Mycobacterium - Phylum Actinomycetota and Kluyvera Phylum Pseudomonadota. Regarding the group of fungi, the prevalence occurred with the genus Mucor identified in most of the treatments sampled. In the genetic sequencing analysis, a greater quantity of beneficial fungi was verified in the T5 treatment, which explains the suppressive activity and the greater length of branches, number of leaves and reduction of cysts of the pearl of the earth occurred mainly in the treatments that received CMM, EMN and other microbial complexes. These results show that the inoculation of beneficial microorganisms can enhance soil ecology, significantly promoting the development of vines and reducing the number of earth pearl cysts. [resumo fornecido pelo autor]
Um dos desafios da agricultura atual é a produção de alimentos com menor interferências junto ao sistema agrícola. A implementação de práticas agrícolas com base ecológica/regenerativas são essenciais para a obtenção de sistemas de produção saudáveis e mais resilientes. Neste sentido o entendimento sobre estratégias de controle da praga Eurhizococcus brasiliensis se faz necessário. O objetivo deste trabalho foi analisar o impacto de diferentes inoculantes sobre o desenvolvimento de Vitis vinifera da cultivar Chardonnay e avaliar a diversidade de microrganismos envolvidos na supressividade de E. brasiliensis. No experimento a campo foram utilizados insumos biológicos por imersão ou aplicação no berço do sistema radicular, por Trichoderma sp, Metarhizium sp, Beauveria bassiana, Paecilomyces fumosoroseus, além de outros compostos como Hidrogel®, Compost Aid®, biofertilizante a base de sementes de mamona, Nem Out®, Microgeo®, CMM - Complexos Microbianos e seus Metabólitos, e EMN - Microrganismos Eficientes Nativos. Foi avaliada a diversidade de microrganismos cultiváveis, identificados pela análise de rDNA 16S, para bactérias e ITS para fungos ou de comunidades microbianas por metagenômica, em material oriundo de fermentados microbianos e em tratamentos de solo. Foram também avaliados comprimento de galhos, número de folhas, população de cistos da pérola da terra e plantas mortas de videira ao final de 22 meses do plantio das mudas. A partir da metodologia de análise dos microrganismos cultiváveis foi possível identificar diferentes grupos de bactérias das amostras de EMN (EM), CMM (FC), solo, SEF (Solo + CMM + EMN) e SFM (Solo + CMM + Microgeo). Os mesmos estão representados principalmente pelos filos Firmicutes, Proteobacteria, seguidos por Mycobacterium e Pseudomonadota dentre outros. Também foram identificados os gêneros Pseudomonas, Acinetobacter e Comamonas, representantes do Filo Proteobacteria, seguidos pelo gênero Mycobacterium - Filo Actinomycetota e Kluyvera Filo Pseudomonadota. Com relação ao grupo dos fungos a prevalência ocorreu com o gênero Mucor identificado na maioria dos tratamentos amostrados. Na análise do sequenciamento genético foi verificado maior quantidade de fungos benéficos no tratamento T5, o que explica a atividade supressiva e o maior comprimento de ramos, número de folhas e redução de cistos da pérola da terra ocorreu principalmente nos tratamentos que receberam CMM, EMN e outros complexos microbianos. Estes resultados mostram que a inoculação de microrganismos benéficos pode potencializar a ecologia do solo, promovendo significativamente o desenvolvimento das videiras e redução do número de cistos da pérola da terra. [resumo fornecido pelo autor]
Keywords: Agricultura orgânica; Pragas - Controle; Uvas - Cultivo; Adubos e fertilizantes; Organic farming; Pests - Control; Viticulture; Manures